2013
DOI: 10.5539/ijbm.v8n4p50
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Commercial Banks in East Africa: A Non Parametric Approach

Abstract: This paper employs Data Envelopment analysis (DEA) to estimate the relative efficiency of selected 58 commercial banks operating within the East African Community, namely Tanzania (11) and Burundi (21). The findings show that most commercial banks in east Africa are operating under a decreasing return to scale. Therefore inefficient utilization of input resources (technical inefficiency) could be one of the reasons for the inefficiency of commercial banks in East Africa; therefore banks should make use of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As described by Choi and Gutierrez [20] banks can partner with the mobile network operators. Raphael [21] argued that the access to financial services in East African countries is very low, especially for the huge population in the rural areas. In Tanzania, for example, one in six Tanzanian have access to financial services from formal Institutions, i.e., over half of the people in Tanzania are excluded from financial services.…”
Section: Related Literaturementioning
confidence: 99%
“…As described by Choi and Gutierrez [20] banks can partner with the mobile network operators. Raphael [21] argued that the access to financial services in East African countries is very low, especially for the huge population in the rural areas. In Tanzania, for example, one in six Tanzanian have access to financial services from formal Institutions, i.e., over half of the people in Tanzania are excluded from financial services.…”
Section: Related Literaturementioning
confidence: 99%
“…For instance, Berger and Humphrey (1992), Kwan and Eisenbeis (1996), Sensarma (2006), Raphael (2012) and Hughes et al (2016) found higher efficiency for large banks over small banks, while the contrary was found by Altunbas et al (2000), Jemric and Vjucic (2002), Rao (2002) and Aiello and Bonanno (2016). Thus, there is a need for further investigation on bank efficiency in this regard.…”
Section: Introductionmentioning
confidence: 84%
“…Measuring and evaluating the productive efficiency of Decision-Making Units (DMUs) requires analytic techniques that provide insights beyond those available in accounting ratio analyses (Peacock et al, 2001;Tahir et al, 2010;Rao and Lakew, 2012;Hatami-Marbini and Toloo, 2019). To make the analysis robust, researchers are using frontier analysis methods.…”
Section: Methodsmentioning
confidence: 99%